Signifikansi Desentralisasi Kehutanan Bagi Implementasi REDD+ di Kabupaten Maluku Tengah - Emilianus Yakob Sese Tolo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
Indonesia is one of the world’s most promising countries for the implementation of policies for reduced deforestation as an element in climate change mitigation. REDD+ has been established as a recognized recipe for international cooperation and economic funds transfer for tropical forest conservation. However, the implementation of REDD+, in Indonesia and elsewhere, is slow to materialize and meets lots of skepticism. Special challenges are related to site selection and opportunity costs, tenure and land conflicts, income distribution, and adjustments to cultural contexts and respect for indigenous peoples’ rights. This paper takes as a starting point some empirical studies of potential implementation of REDD+ projects in Maluku Tengah district, Indonesia. We conclude that REDD+ implementation will enhance elogical and economic benefits in the society. The paper will then discuss how forest decentralization needs to be promoted to facilitate for REDD+ implementation in Indonesia.